Śląska Biblioteka Publiczna w 1945 roku (w świetle dokumentów z Archiwum Zakładowego) (PDF 921 KB) (Książnica Śląska, 2025)
On the basis of documents from the archives of the Biblioteka Śląskathe author presents the particularly interesting fate of the Śląska Bi-blioteka Publiczna in 1945. She describes the library’s situation afterthe cessation of the hostilities, the scale of the material damages andthe losses in its collection. She also discusses the post-war securingof libraries and library collections, and the efforts of the employeesto restore access to collections as soon as possible.